ANALISIS PENGARUH MOTIVASI, ORGANISASI DAN SOFT SKILL TERHADAP KINERJA MAHASISWA FAKULTAS TEKNIK UNIKA ATMAJAYA ANGKATAN 2012 - Andre Sugioko; Trifenaus Prabu Hidayat; Maria Goretti Yostiana Putri (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
College Students as the input of a university, have different attitudes and learning outcomes from one another. Education as one way to achieve the goal, can be assessed and seen through the performance. The performance is in question is the achievement of a student focusing on college events. The performance of the students in college year not rated academically, but also nonacademic. According to some studies, the performance can be assessed with motivation, organization and soft skills. This study aims to measure the influence of motivation, organization, and soft skills of the students' performance. The focus of this research is a student in the fourthyear college or the student class of 2012, which is considered to have a lot of experience that can be measured in this study. Processing data using Structural Equation Modeling with Amos. The results of this study are, Motivation has an influence on student performance, while the Organization and Soft skills have no effect on student performance.